Experimental Study on the Thermal Behavior of Building Materials in A Dry and Arid Climate - Oussama, Benali; Abdelmadjid, Dobbi; Noureddine, Hassini (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper analyzes the performance of material constructions in two small cubicle rooms during hot and cold periods, based on the results of experiments conducted at the University of Ouargla in southeastern Algeria. The climatic conditions in this region are extreme. The outdoor ambient temperature varies between 47 C° during the day and 30 C° at night for the hot period, and between 16 C° during the day and -1 C° at night for the cold period. The rooms of the in-situ cubicles were identical with a dimension of 1 m × 1 m × 1 m. The walls of the stone cubicles were made with Ouargla stone (15 cm) and two layers of gypsum (1.5 cm), and for brick, the walls of the cubicles were made with hollow brick (15 cm) and two layers of mortar (1.5 cm). Measurements are made of ambient temperatures, wall temperatures, and instantaneous heat flux densities through the walls. The effect of building material selection on energy consumption was also studied. During two different periods (August 28-30, 2020) and (October 21-23, 2020), the construction with stone decreased the indoor temperature by approximately 6 °C during the day and reduced the apparent thermal mass of the room in the first period, but in the second period, the indoor temperature increased by approximately 1 °C. The residential scale confirmed that Ouargla stone improves thermal comfort by providing high insulation and reducing indoor temperature oscillations. This material is abundant in nature and can be easily extracted and used directly in constructing houses without recycling it, which helps reduce CO2 emissions.